Isolation of cellulose fibers from coconut husk and banana peels and preparationof cellulose nanocrystals from whatman filter paper - Bashela Carol, anak Roger. (Universiti Malaysia Sarawak (UNIMAS), 2008)
The objectives of this study are to prepare and characterize the cellulose fibers from coconut husk and banana peels. Two different methods for isolation of cellulose from coconut husk and banana peels were studied. Isolation by the delignification by 1.3% sodium chlorite followed by alkali (10 & 17.5% NaOH) gave cellulose yields 73-74% cellulose for coconut and 39-40% for banana peels. Treatment with 80% acetic and 70% & 40% nitric acid yielded about 67-77% of cellulose for coconut husk and 34-35% for banana peels. The pure cellulose fibres (Whatman No.1) used for preparation on cellulose nanocrystal suspension was done using the maceration procedures with hydrogen peroxide and acetic acid (I: I, v/v) in 70°C for several days. Both cellulose fibers and nanocrystal suspension were characterized using FfIR-spectroscopy, CHN elemental analyzer, SEM, TEM and Optical microscope.